2004
DOI: 10.1111/j.1601-0825.2004.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Oro‐facial lesions and CD4 counts associated with HIV/AIDS in an adult population in Oyo State, Nigeria

Abstract: The type of oro-facial lesions most commonly associated with HIV/AIDS in Oyo state, Nigeria, has been shown to be pseudomembranous oral candidiasis. This was followed by angular cheilitis. These lesions, although found in HIV-negative subjects, were in a lower proportion as compared with HIV-positive subjects. Mean CD4 counts were lower in HIV-positive subjects and this was associated with greater prevalence of oro-facial candidiasis and angular cheilitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
4
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 44 publications
5
29
4
4
Order By: Relevance
“…Oral candidiasis was the commonest lesion observed in this study population, agreeing with findings by Bodhade et al (39.3%), Kardpon et al (55%), Adrogubangba et al (33.3%) and Allan et al (17.7%) [12, 15, 20, 21]. The pseudomembranous subtype was the commonest, just as was observed in south western Uganda (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Oral candidiasis was the commonest lesion observed in this study population, agreeing with findings by Bodhade et al (39.3%), Kardpon et al (55%), Adrogubangba et al (33.3%) and Allan et al (17.7%) [12, 15, 20, 21]. The pseudomembranous subtype was the commonest, just as was observed in south western Uganda (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…19 In the present study, the prevalence of HIV-OL was strongly associated (p = 0.007) with low CD4 + levels (usually less than 200 cells/mm 3 ). Similarly to our results, Adurogbangba et al 20 reported a strong association between HIV-OL and low CD4 + counts, mainly when the latter were below 500 cells/mm 3 . As with CD4 + counts, viral load is also related to oral manifestations.…”
Section: Cd4supporting
confidence: 92%
“…Analysis of oral lesions in 81 HIV-positive subjects and 31 HIV-negative subjects and their CD4+ counts in a study done at Oyo, Nigeria has shown that CD4+ counts < 500 cells/ml were significantly associated with having pseudomembranous candidiasis and angular cheilitis. [27] Another study,[21] reported oral candidiasis and melanotic hyperpigmentation could be used as markers of immunosuppression depicted by CD4+ counts < 200 cells/ml while oral hairy leukoplakia could indicate HIV-ribonucleic acid ≥ 20,000 copies/ml in an adult Nigerian population. Similarly, this study revealed that the presence of oral candidiasis and hairy leukoplakia were associated with CD4+ counts < 200 cells/ml.…”
Section: Discussionmentioning
confidence: 99%